The basics of information security : understanding the fundamentals of InfoSec in theory and practice - Andress, Jason (Amsterdam ; Boston : Elsevier/Syngress, Syngress is a imprint of Elsevier, 2014)
"The Basics of Information Security will provide the reader with a basic knowledge of information security in both theoretical and practical aspects. We will first cover the basic knowledge needed to understand the key concepts of information security, discussing many of the concepts that underpin the security world. We will then dive into practical applications of these ideas in the areas of operations, physical, network, operating system, and application security. Book Audience This book will provide a valuable resource to beginning security professionals, as well as to network and systems administrators. The information provided on can be used develop a better understanding on how we protect our information assets and defend against attacks, as well as how to apply these concepts practically"--
Keywords: Computer security; Computer networks -- Security measures; Information resources management